2016
DOI: 10.1186/s12890-016-0308-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of bridging to lung transplantation with antifibrotic drugs in idiopathic pulmonary fibrosis: a case series

Abstract: BackgroundFollowing recent approval of pirfenidone and nintedanib for idiopathic pulmonary fibrosis (IPF), questions arise about the use of these antifibrotics in patients awaiting lung transplantation (LTx).MethodsSafety and efficacy of antifibrotic drugs in IPF patients undergoing LTx were investigated in a single-centre retrospective cohort analysis.ResultsA total of nine patients, receiving antifibrotic therapy for 419 ± 315 days until subsequent LTx, were included. No major side effects were noted. Signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 18 publications
1
44
0
3
Order By: Relevance
“…Following lung transplant, pirfenidone was administered successfully in a woman who experienced progressive allograft dysfunction [47]. In another single-centre, retrospective analysis at a large-volume transplant centre, seven patients receiving pirfenidone underwent lung transplant with no serious post-operative AEs observed and no major drug interactions with other perioperative medications [44]. These experiences suggest that pirfenidone can be safely administered before lung transplant with good long-term outcomes.…”
Section: Ae Management In Specific Patient Subgroupsmentioning
confidence: 78%
See 1 more Smart Citation
“…Following lung transplant, pirfenidone was administered successfully in a woman who experienced progressive allograft dysfunction [47]. In another single-centre, retrospective analysis at a large-volume transplant centre, seven patients receiving pirfenidone underwent lung transplant with no serious post-operative AEs observed and no major drug interactions with other perioperative medications [44]. These experiences suggest that pirfenidone can be safely administered before lung transplant with good long-term outcomes.…”
Section: Ae Management In Specific Patient Subgroupsmentioning
confidence: 78%
“…Currently there are no established guidelines regarding pirfenidone therapy in perioperative lung transplant [44]. Several case studies of pirfenidone use have been reported.…”
Section: Ae Management In Specific Patient Subgroupsmentioning
confidence: 99%
“…A pre-clinical lung transplantation study in rats revealed no evidence of impaired wound healing despite nintedanib being administered before and after the surgical procedure [44] and a small case study in Belgium (nintedanib, n = 2) showed no problems with bleeding or delayed wound healing related to anti-fibrotic treatment. There were some mild complications with anastomosis between the transplanted organ and the trachea in some patients; however, these were mild or uneventful [45]. A second retrospective study in Italy (nintedanib, n = 9), inclusive of data from 3 different transplant centers, also reported no problems with postoperative bleeding or thoracic wound healing [46].…”
Section: Expert Statements and Recommendationsmentioning
confidence: 99%
“…No major side-effects occurred during the observation period, except for a significant weight loss due to drug-induced anorexia. Moreover, FVC values tended to stabilise after 12 weeks of treatment in most patients, and no post-operative thoracic wound healing problem, bleeding or severe anastomotic airway complications due to prior antifibrotic treatment were described [35]. Therefore, although only evaluated in a very limited number of case studies, antifibrotic drugs have been shown to be safe in IPF patients undergoing lung transplantation.…”
Section: When To Stop Therapymentioning
confidence: 99%
“…According to the most recent clinical trials evaluating antifibrotic drugs (2832 patients), only 11 patients, treated with pirfenidone, received transplants, and specific data on their outcomes are lacking. A recent study by DELANOTE et al [35] focused on this specific problem, and published the largest clinical series available. Nine patients with IPF treated with pirfenidone (n=7) or nintedanib (n=2) for a mean period of 13.4 months, who underwent lung transplantation, were evaluated for a median post-transplant follow-up of 19.8 months.…”
Section: When To Stop Therapymentioning
confidence: 99%